2021
DOI: 10.3390/en14144079
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning—A Review of Applications in Mineral Resource Estimation

Abstract: Mineral resource estimation involves the determination of the grade and tonnage of a mineral deposit based on its geological characteristics using various estimation methods. Conventional estimation methods, such as geometric and geostatistical techniques, remain the most widely used methods for resource estimation. However, recent advances in computer algorithms have allowed researchers to explore the potential of machine learning techniques in mineral resource estimation. This study presents a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 142 publications
0
8
0
Order By: Relevance
“…Overall, the utilization of remote sensing information and neural network modelling has enhanced the accuracy of pollutant measurement, feature extraction, and identification system construction in brownfield recognition, along with improved accessibility to multi-source and multi-temporal data. Certainly, we also need to consider that certain brownfields do not represent vast areas or extensive industrial sites with a multitude of samples suitable for applying geostatistics and Machine Learning techniques [ [105] , [106] ]. In the future, identifying brownfields with specific spatial locations, properties, and characteristics will require further exploration and research into alternative approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the utilization of remote sensing information and neural network modelling has enhanced the accuracy of pollutant measurement, feature extraction, and identification system construction in brownfield recognition, along with improved accessibility to multi-source and multi-temporal data. Certainly, we also need to consider that certain brownfields do not represent vast areas or extensive industrial sites with a multitude of samples suitable for applying geostatistics and Machine Learning techniques [ [105] , [106] ]. In the future, identifying brownfields with specific spatial locations, properties, and characteristics will require further exploration and research into alternative approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional estimation methods, such as geometric and geostatistical techniques, continue to be widely used. Nevertheless, the latest developments in computer algorithms have empowered researchers to explore the potential of employing machine learning techniques for mineral resource estimation [175]. In the same year, A. Raza published a paper on fault diagnosis techniques in power transmission systems.…”
Section: Recent Developments-using Autonomous Processesmentioning
confidence: 99%
“…Regardless, a recent surge in research and development over the last few years has shown that ML techniques can be successfully applied to a broad spectrum of the mineral value chain, from greenfield exploration through to production, mine closure and site reclamation. There are a number of review papers available that summarize a variety of ML applications in the mining space (e.g., [49,50,[67][68][69]), including mineral exploration and resource evaluation, strategic mine planning, machine operations and related automation, drilling and blasting optimization and ore beneficiation, among others. However, there is little published work related to the integration of ML techniques into mine-to-mill framework strategies.…”
Section: Appendix Amentioning
confidence: 99%
“…Recent reviews have shown that neural networks and deep learning models account for ~25% of all ML approaches used in the mining space, with support vector machines (23%) and ensemble methods (22%) close behind [67]. ANNs have been especially useful in mineral resource estimation (e.g., [85][86][87]), comprising ~46% of the ML techniques used in this area [68]. Other prominent applications include mineral prospecting and mapping [88,89], geophysics and remote sensing [90,91], ore classification [92,93], drilling and blasting operations [94,95], mining method selection, equipment utilization and production planning [96,97], ore beneficiation and mineral recovery [98,99] and mine site reclamation [100,101], among others.…”
Section: Appendix B3 Mlp Design Training and Mining Applicationsmentioning
confidence: 99%